Clinical Outcomes Comparison of Combined Small Incision Lenticule Extraction with Collagen Cross-Linking Versus Small Incision Lenticule Extraction Only. (11th October 2022) - Chabib, Ayoub; Mammone, Massimo; Fantozzi, Chiara; Lian, Rebecca R.; Afshari, Natalie A.; Goldbaum, Michael H.; Fantozzi, Marco
Abstract : Purpose . To evaluate clinical outcome during 24 months follow-up between small incision lenticule extraction combined with cross-linking (SMILE Xtra) and small incision lenticule extraction (SMILE) only. Setting . Ophthalmology Division of San Rossore Medical Center, Pisa, Italy. Design . Retrospective comparative case series. Methods . The study comprised 70 eyes (35 patients); 40 eyes were corrected using SMILE and 30 eyes were corrected using SMILE Xtra using a low energy protocol. The outcomes were compared at 1, 6, 12, and 24 months postoperatively. Results . The mean spherical equivalent (SEQ) reduced from −7.18 ± 1.21 D to −0.01 ± 0.09 D in the SMILE group and from −6.20 ± 2.99 D to −0.04 ± 0.1 D postoperatively in SMILE Xtra (p < 0.05 ). At 24 months the mean SEQs were −0.01 ± 0.24 D for SMILE and −0.15 ± 0.33 D for SMILE Xtra (p > 0.05 ). At 1, 6, 12, and 24 months, there were no statistically significant differences between the SMILE and SMILE Xtra groups in logarithm of the minimum angle of resolution (logMAR) uncorrected distance visual acuity (UDVA), safety, and efficacy index (p > 0.05 ). The mean average keratometry ( K -avg) at 1, 6, 12, and 24 months after surgery did not shown any statistically significant difference between SMILE and SMILE Xtra group (p > 0.05 ). The mean maximum keratometry ( K -max) readings at 1, 6, 12, and 24 months were not statistically significant between SMILE and SMILE Xtra group (p > 0.05 ). The preoperative mean thinnest point pachymetry (TTP) was 543.90 ± 22.85  μ m in the SMILE group and 523.40 ± 37.01  μ m in the SMILE Xtra group (p < 0.05 ). At 1, 6, 12, and 24 months the mean TTP was not statistically significant between the SMILE and SMILE Xtra groups (p > 0.05 ). At 24 months, the TTP was 408.29 ± 38.75  μ m for the SMILE group and 402.22 ± 37  μ m for the SMILE Xtra group (p > 0.05 ). In the preoperative period, the mean maximum posterior elevation (MPE) was 8.63 ± 4.35  μ m for SMILE and 8.13 ± 2.54  μ m for SMILE Xtra (p > 0.05 ). After the surgical procedure, both groups showed a statistically significant increase of the MPE (p < 0.05 ). At 24 months, the MPE was 11.00 ± 4.72  μ m for SMILE Xtra and 10.14 ± 3.85  μ m for the SMILE group (p > 0.05 ). In the preoperative period, the means of the root mean square (RMS) of high-order aberration (HOA) were 0.08 ± 0.03  μ m for the SMILE group and 0.08 ± 0.03  μ m for the SMILE Xtra group (p > 0.05 ). At 24 months, the RMS of HOA was 0.13 ± 0.07  μ m for the SMILE group and 0.14 ± 0.07  μ m for the SMILE Xtra group (p > 0.05 ). In the preoperative period, the root mean square of coma aberration (RMS-Coma) aberration was 0.06 ± 0.09  μ m for the SMILE group and 0.04 ± 0.03  μ m for the SMILE Xtra group (p > 0.05 ). At 24 months, the coma aberration of SMILE group was 0.12 ± 0.21  μ m and 0.16 ± 0.25  μ m for SMILE Xtra group (p > 0.05 ). Conclusions . SMILE Xtra procedure is a safe and simple procedure that can be offered to patients with high corneal ectasia risk because there were no differences in the indices of ectasia compared to the group treated only with SMILE which has a low corneal ectatic risk.